Strategi Respectful Maternity Care: Mengurangi Stigma dan Meningkatkan Penerimaan terhadap Ibu Hamil Remaja - Syafitasari, Juanda; Putri, Poppy Siska; Aprilia, Resya (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Adolescent pregnancy, particularly unintended pregnancy, continues to pose serious challenges with multifaceted health, psychological, and social implications. In Indonesia, adolescent mothers are not only at risk of medical complications but also experience stigma, moral judgment, and discrimination from society and healthcare providers. This study aimed to explore the lived experiences of pregnant adolescents concerning stigma and to examine the role of Respectful Maternity Care (RMC) in enhancing acceptance and the quality of midwifery services. A qualitative study was conducted using an interpretive paradigm and phenomenological design. Participants included ten pregnant adolescents with a history of unintended pregnancy as key informants, supported by parents, midwives, and the head of a community health center. Data were collected through in-depth interviews and Focus Group Discussions (FGDs), and analyzed thematically following the Standards for Reporting Qualitative Research (SRQR). Five major themes emerged: (1) social stigma as a primary barrier; (2) family support as a protective factor; (3) experiences of discrimination in healthcare services; (4) empathetic care practices based on RMC; and (5) the need for systematic RMC strategies. Findings highlight that stigma and discrimination hinder adolescents’ access to healthcare, while RMC fosters safety, inclusion, and social support. Social stigma and healthcare discrimination remain significant barriers for pregnant adolescents in Indonesia. The implementation of RMC has the potential to enhance acceptance, strengthen family and community support, and improve maternal health outcomes. It is recommended that healthcare providers strengthen empathetic communication, policymakers develop adolescent-friendly care protocols, and communities receive targeted education to reduce stigma. Keywords: Stigma, Pregnant Women, Adolescents, Respectful Maternity Care, Acceptance.  ABSTRAK Kehamilan remaja, terutama yang tidak diinginkan, masih menjadi tantangan serius dengan implikasi kesehatan, psikologis, dan sosial yang kompleks. Di Indonesia, remaja hamil tidak hanya berisiko terhadap komplikasi medis, tetapi juga menghadapi stigma, penghakiman moral, serta diskriminasi dari masyarakat maupun tenaga kesehatan. Penelitian ini bertujuan menggali pengalaman remaja hamil terkait stigma yang dialami serta menelaah peran Respectful Maternity Care (RMC) dalam meningkatkan penerimaan dan kualitas pelayanan kebidanan. Penelitian kualitatif dengan paradigma interpretif dan desain fenomenologi. Informan terdiri dari sepuluh remaja hamil dengan riwayat kehamilan tidak diinginkan sebagai informan kunci, serta orang tua, bidan, dan kepala puskesmas sebagai informan pendukung. Data dikumpulkan melalui wawancara mendalam dan Focus Group Discussion (FGD), kemudian dianalisis secara tematik dengan mengacu pada Standards for Reporting Qualitative Research (SRQR). Penelitian menemukan lima tema utama: (1) stigma sosial sebagai hambatan utama; (2) dukungan keluarga sebagai faktor protektif; (3) pengalaman diskriminasi dalam pelayanan kesehatan; (4) praktik pelayanan empatik berbasis RMC; dan (5) kebutuhan strategi sistematis RMC. Stigma dan diskriminasi terbukti menghambat akses layanan, sementara penerapan RMC menumbuhkan rasa aman, dukungan sosial, dan pelayanan yang lebih inklusif. Stigma sosial dan diskriminasi masih menjadi hambatan signifikan bagi remaja hamil dalam memperoleh layanan kesehatan. Implementasi RMC berpotensi meningkatkan penerimaan, memperkuat dukungan keluarga dan masyarakat, serta memperbaiki luaran kesehatan maternal. Disarankan tenaga kesehatan memperkuat praktik komunikasi empatik, pemerintah menyusun SOP pelayanan ramah remaja, dan masyarakat memperoleh edukasi untuk mengurangi stigma. Kata Kunci: Stigma, Ibu Hamil, Remaja, Respectful Maternity Care, Penerimaan